Utilization of atis (Annona squamosa L.) pulp as a pasteurized fruit beverage. - Jegonia, Jaira Marie Ybiernas
Atis (Annona squamosa L.) is an underutilized tropocal fruit which is primarily consumed as fresh. A Atis fruit is highly perishable that it cannot be stored for a long time. Atis is rich in nutrients and it has an immense potential to be processed into a product. Three formulations of pasteurized Atis juice were prepared with varying amounts of Atis extract to water. The three formulations made were 25% Atis extract: 75%H20, 50% Atis extract: 50%:H2O, and 75%Atis extract: 25%H2O. Formulation 3 with 75% Atis extract to 25% water was chosen as the Most Preferred Formulation (MPF). The sensorial properties of the MPF were found to have a very distinct Atis flavor, a distinct Atis odor, a smooth texture, and a cloudy white color. The MPF was found to have a pH of 4.54±0.2 and a TSS of 23.02±0.1. Vitamin C content of the MPF is 4.84±1.0% and total sugar content is 31.44±3.0%. In terms of microbial quality, the Total Plate Count and Yeast and Molds Count of the Pasteurized MPF of Atis juice are below the standard maximum count for juices set by Gulf Standards 2000 and is therefore microbiologically safe for consumption. In conclusion, Atis fruit can be processed into a pasteurized fruit beverage. Further studies may invilve proximate analysis, general acceptability of the product, and storage study.